Efficacy of Intrathecal 0.75% Hyperbaric Ropivacaine versus 0.5% Hyperbaric Bupivacaine for Elective Inguinal and Perineal Surgery: A Randomised Double-blinded Clinical Study - Bhavini Shah; Dipanjali Mahanta (Journal of Clinical and Diagnostic Research)
Introduction: Ropivacaine, an amide local anaesthesia, often considered safer alternative to bupivacaine. Bupivacaine, a longer-acting agent that provides dense motor blockade, is known to carry a higher risk of re-entrant arrhythmias and cardiac depression with accidental intravascular injection. The shorter duration of action, coupled with profound sensory block and comparatively less side-effects, makes ropivacaine useful in tackling cases of day care surgery. Aim: To compare the efficacy of hyperbaric ropivacaine versus bupivacaine for elective inguinal and perineal surgery under spinal anaesthesia in terms of time of sensory and motor block, time taken to reach peak T8 level sensory block, total duration of both sensory and motor block, time of first micturition, and any associated side-effects. Materials and Methods: The present randomised double-blind clinical study, was carried out in the Department of Anaesthesia, Dr. D. Y Patil Medical College, Hospital and Research Centre (tertiary healthcare centre), Pune, Maharashtra, India, from March 2023 to August 2023. Study involved 30 patients aged 18-60, classified as American Society of Anaesthesiologists (ASA) grade I and II. Patients were randomly assigned to group RH (receiving hyperbaric ropivacaine) or group BH (receiving hyperbaric bupivacaine). The study assessed for onset and duration of sensory block at T-8 dermatome. The study also assessed motor block onset and duration using modified Bromage scale, observing postoperative micturition, intraoperative haemodynamic changes and adverse effects. Statistical analysis was performed using Statistical Package for the Social Sciences (SPSS) software version 16.0, with a p-value of <0.05 considered significant. Results: Demographic profile in terms of age {Mean±Standard Deviation (SD) in group RH: 42.93±14.73 years vs group BH: 39.06±11.94 years), gender distribution, type of surgery performed and its duration (group RH: 85.67±39.5 minutes vs group BH: 98.4±32.8 minutes) was not significant. The onset of sensory block (2.09±0.69 min) and motor block (3.52±0.66 min), the time taken to reach T8 level (3.40±0.93 min), was faster in the hyperbaric ropivacaine group. Similarly, the duration of motor block (261.93±73.21 min), time taken for the recession of the sensory block to S2 (351.4±66.78 min), and the recession of the motor block to Bromage scale 0 (291.93±64.93 min) were faster in ropivacaine group. The time taken for the passage of first micturition post-subarachnoid block was earlier (338.73±31.29 min) in ropivacaine group. Conclusion: A 0.75% hyperbaric ropivacaine is more efficacious, with faster onset of sensory and motor blockade, relatively quick recovery profile, and an earlier time of first micturition in comparison to 0.5% hyperbaric bupivacaine.